Gut microbiomes of cyprinid fish exhibit host-species symbiosis along gut trait and diet - Liu, Yaqiu; Li, Xinhui; Li, Yuefei; Li, Jie; Zhu, Shuli (Frontiers in Microbiology, 2022)
Teleost omnivorous fish that coexist partially sharing resources are likely to modify their gut traits and microbiome as a feedback mechanism between ecological processes and evolution. However, we do not understand how the core gut microbiome supports the metabolic capacity of the host and regulates digestive functions in specialized omnivorous fish gut traits. Therefore, we evaluated the gut microbiome of eight omnivorous fish from a single family (i.e., Cyprinidae) in the current study. We examined the correlation between host phylogeny, diet composition and intestinal morphological traits related to the intestinal microbiome. The results indicated that cyprinid fish with similar relative gut lengths had considerable gut microbiome similarity. Notably, SL (short relative gut length) group, as zoobenthos and zooplankton specialists, were abundant in Proteobacteria and were less abundant in Firmicutes than in the ML (medium relative gut length) and LL (long relative gut length) groups. These fish could extract nutrients from aquatic plant and algae. Additionally, we found the relative abundance of Clostridium and Romboutsia to be positively correlated with host relative gut length, but negatively correlated with the relative abundance of Cetobacterium, Plesiomonas, Bacteroides, and Lactobacillus and host relative gut length. We also show a positive linear relationship between host gut microbiome carbohydrate metabolism and relative gut length, while the amino acid and lipid metabolism of the gut microbiome was negatively correlated with host relative gut length. In addition, omnivorous species competing for resources improve their ecological adaptability through the specialization of gut length, which is closely related to variation in the synergy of the gut microbiome. Above all, specialized gut microbiota and associated gut morphologies enable fish to variably tolerate resource fluctuation and improve the utilization efficiency of nutrient extraction from challenging food resources.